Characteristic Analysis of Indonesian Low and Medium Rank Coals and Their Influence on Carbon Dioxide Adsorption Capacity - Ramdhani, Muhammad Rizki; Yan Rizal R; Sigit Arso Wibisono; Soleh Basuki Rahmat; Muhammad Abdurachman Ibrahim; Eko Budi Cahyono (Geological Agency, 2024)
Indonesia has great deep-seated coal potential , such as Lakat coal and Muaraenim coal, which can be utilized as a medium for Carbon Capture and Storage (CCS). These coals vary in characteristic which affects their ability to adsorb or store carbon dioxide gas (CO2). The moisture content of the Lakat coal is less than that of the Muaraenim coal, while the ash content of Lakat coal is 4-5 times higher than the Muaraenim coal. Lakat coal contains more vitrinite content than Muaraenim coal, while Muaraenim coal contains more inertinite content than Lakat coal. The CO2 gas adsorption capacity of Muaraenim coal is 37.62 cc/g which higher than Lakat coal (31.56 cc/g) on dry ash-free basis. The adsorbed CO2 is negatively correlated with vitrinite reflectance, ash content, and moisture content in both coals. The correlation between maceral composition (vitrinite and inertinite content) and adsorbed CO2 content differs between these coals. These analyses will support the CCS/CCUS study in deep seated coal seams by providing the information of CO2 maximum holding capacity in coal and their relationship to its chemical and organic composition.